Perlindungan Data Pribadi Melalui Undang-Undang Nomor 27 Tahun 2022: Jawaban Tantangan Cybercrime Era Globalisasi Serba Digitalisasi - Utomo, Setyo (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
This research was conducted due to the urgency of massive technological and information developments in Indonesia. These developments have been accompanied by negative impacts in the form of cybercrime targeting people's personal data. Law enforcement must be in line with the realities of the times. The problems addressed and discussed in this study are how personal data protection has developed through Law No. 27 of 2022 and how Law No. 27 of 2022 is urgently needed to meet public demands for personal data protection. The method used is normative juridical, using primary data. Literature sources were searched using a literature study. The results of this study show that the Indonesian government, through Law Number 27 of 2022, guarantees the privacy and personal data rights of citizens as one of the human rights protections. Furthermore, this personal data protection law harmonizes Indonesia's personal data protection regulations with international standards. Sanctions for violations of personal data protection provisions are also stated more explicitly in this law.